Fermentation of non-digestible raffinose family oligosaccharides and galactomannans by probiotics. Issue 3 (21st February 2018) - Zartl, Barbara; Silberbauer, Karina; Loeppert, Renate; Viernstein, Helmut; Praznik, Werner; Mueller, Monika
Abstract : This study demonstrates the α-galactosidase activity and the growth of 20 selected probiotic strains with non-digestible raffinose family oligosaccharides and galactomannans. Abstract : Due to their prebiotic potential indigestible oligosaccharides became a major focus of research interest. In this study the growth of selected probiotic strains including lactobacilli, bifidobacteria, Lactococcus lactis, Streptococcus salivarius ssp. thermophilus, Pediococcus ssp. and Enterococcus faecium with the, raffinose family oligosaccharides (RFOs) raffinose, stachyose and verbascose and galactomannan from guar bean Cyamopsis tetragonoloba (total guar carbohydrates, oligosaccharides (dp 2–4) and polysaccharides (dp > 5), obtained by size exclusion chromatography) were tested by means of turbidity measurements. RFOs were used by 75% of all strains, with some delay for the trisaccharide raffinose and the tetrasaccharide stachyose and a limited fermentation of the pentasaccharide verbascose. L. reuteri, P. pentosaceus and B. lactis HNO19™ were able to ferment not only raffinose and stachyose but also verbascose. Guar oligosaccharides were fermented by 15 out of 20 strains; P. acidilactici, L. acidophilus, L. rhamnosus GG and B. animalis ssp . lactis BB12 metabolized them comparably well as glucose or galactose. Isolated guar polysaccharides were not fermented whereas total guar carbohydrates were fermented by 7 strains, apparently caused by the oligosaccharide content. The findings of this study may be important for functional food products especially for indigestible oligosaccharides which may cause adverse effects in the gut when not cleaved.